Hemodynamics of the corpus luteum in mares during experimentally impaired luteogenesis and partial luteolysis - Ferreira, J. C. [UNESP]; Filho, L.F. Novaes [UNESP]; Boakari, Y. L. [UNESP]; Canesin, H. S. [UNESP]; Thompson, D. L.; Lima, F. S.; Meira, C. [UNESP] (Elsevier, 2018)
The aim of the current project was to characterize the luteal vascularity and the plasma concentrations of progesterone (P4), prolactin (PRL) and 13,14-dihydro-15-keto-PGF2α (PGFM) in mares with luteal disturbances during early and mid-diestrus. In Experiment 1, twenty-one mares were treated with 2 mL of 0.9% NaCl, or 1 mg Dinoprost, or 10 mg Dinoprost on day two after ovulation (Control-D2, 1/10PGF-D2 and PGF-D2 groups, respectively; n = 7 mares/group). In Experiment 2, similar treatments were performed eight days post-ovulation using a different cohort of 21 mares (Control-D8, 1/10PGF-D8 and PGF-D8 groups, respectively; n = 7 mares/group). Blood samples were collected hourly and power-Doppler examinations of the corpus luteum (CL) were performed every 6 h from H0 (moment immediately before treatment) to H48. Data collection was also done once a day from D0 (day of ovulation) to D20. In Experiment 1, the PGF-D2 and 1/10PGF-D2 groups had lower increase of plasma concentration of P4 until H48 and reduced maximum P4 concentrations on D8-D11 than mares from the Control-D2 group. However, no differences among groups were detected for luteal vascularity during early and mid-diestrus. In Experiment 2, complete and partial luteolysis were detected in mares from the PGF-D8 and 1/10PGF-D8 groups, respectively. Luteal vascularity and plasma P4 concentrations differed among Control-D8, PGF-D8 and 1/10PGF-D8 groups on H48. Partially regressed CLs (1/10PGF-D8 group) generated more Doppler signals than completed regressed CLs (PGF-D8 group) between D10 and D13. In both experiments, a transient increase in PRL activity was observed in parallel to the PGFM pulse in mares receiving 1 or 10 mg Dinoprost. The use of prostaglandin on D2 at conventional or 1/10 of the dose impaired the luteal development in mares. Moreover, the low dose of prostaglandin lead to partial regression of mature CLs. The blood supply was reduced in partially regressed CLs, but not in CLs undergoing impaired luteogenesis.
Keywords: Diestrus; Doppler ultrasonography; PGFM; Progesterone; Prolactin